Client/server job scheduling rediscovered. - Vinzant, David (American City & County, 1997)
Government sector attempts to optimize the strengths of mainframe and client/server environments to achieve efficient computing are being made successful by job scheduling. The strategy offers a flexible automation solution, increasing productivity and helping to guarantee the satisfaction of both internal and external customers. The strategy, which is new to the networking environment, is based on the strengths of mainframe batch processing and offers greater depth in functionality.